Social media use and Ghanaian family values : a study in northern region of Ghana - Adam, Iliasu (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
The purpose of this study is to examine social media use and family social values, using the media richness theory: A study in Northern Region of Ghana. The study employed mixed method (explanatory sequential design) to examine the influence of social media use on family values in the Northern Region of Ghana where the use of social media is perceived as threatening family values and social relations of family members. Quantitative data collection, which was the dominant methodology was carried out first and then subsequent focus group discussions to supplement. About 1,200 questionnaires were administered to respondents in two rural districts and one urban metropolis. A total of 47 participants took part in the focus group discussions. The respondents were categorised as family heads, mothers and Generation Y (youth). IBM SPSS 24 was used for the descriptive statistics, factor analysis and reliability test. Structural equation model (SEM) was used to examine the relationship between the independent variables and dependent variable and tested the hypothesised model. The model was validated and indicated acceptable psychometric features in terms of reliability, and the feasibility of the path coefficients. The results indicate there were not considerable differences in the opinion toward the richness and perception of social media use in family communication between rural/urban communities, gender, education level, generation gap and income level groups. Six focus group discussions were held with two group discussions for each category (family heads, mothers and Generation Y). Based on the thematic analysis, 12 salient themes were extracted from the focus group discussions and the results were in synch to the quantitative findings. This underpinning theoretical framework for the study is Media Richness Theory to ascertain the richness and perception of social media use as a medium of communication by family members, and in illuminating the context of social media richness in the context of family values. The findings from the quantitative and qualitative corroborated each other, indicating that the use of social media in family communication has the attributes of rich media. The attributes are immediate feedback, personalised messages, language variety, plus availability of a number of cues and channels, such as voice and visuals. The study also showed that though the uses of social media have reduced visits among family members, it has not negatively affected their family values. This study provides several perspectives on new communication technologies and their impact on family culture in Ghana. Such a culture-specific approach to Media Richness study enlightens us on the cultural dimensions of social media using the family unit as a focus of analysis. It would be very valuable in informing the work of policymakers, development practitioners, educators and African communication scholars on the understanding of new media technologies and the influence they are having on social interaction within family members. Media richness studies could explore different settings, contexts, samples, and variables to contribute towards the improvement of the theory in lieu of advancement of technology and changing structure of the society.